Principal and Teacher Shared Race and Gender Intersections: Teacher Turnover, Workplace Conditions, and Monetary Benefits - Samantha Viano; Luis A. Rodriguez; Seth B. Hunter (SAGE Publishing, 2023)
Recruiting racially minoritized principals is one suggested strategy to increase the racial diversity of teachers, who would then better match their increasingly racially diverse students. However, focusing solely on race ignores the salience of race-gender intersectionality in principal-teacher relations. Using three waves of nationally representative, cross-sectional data with school and year fixed effects, we compared similar teachers in the same school who are and are not race-gender congruent with their principal. We found that better discretionary workplace benefits were concentrated among Black teachers with Black principals, especially Black male teachers with Black male principals, who reported workplace supports almost half a standard deviation higher than did similar non-Black female teachers in their school. Male teachers earned up to $2,890 more supplemental income with male, racially congruent principals; female teachers earned up to $1,050 less with female, racially congruent principals. However, teacher turnover was not consistently responsive to race-gender congruence.